Core-shell expandable graphite @ aluminum hydroxide as a flame-retardant for rigid polyurethane foams. (December 2017) - Wang, Yintao; Wang, Feng; Dong, Quanxiao; Xie, Mingchen; Liu, Peng; Ding, Yanfen; Zhang, Shimin; Yang, Mingshu; Zheng, Guoqiang
Abstract: To enhance the flame-retardant performance of expandable graphite (EG) in rigid polyurethane foam (RPUF), EG particles were encapsulated with inorganic nanoparticles, namely aluminum hydroxide (ATH), forming complex particles EG@ATH with core-shell structure. After the deposition of ATH shell, the expandability of the particles was enhanced from 163 to 197 ml/g, leading to better flame-retardant performance in RPUF. At a content of 11.5 wt%, the limited oxygen index could be increased from 21.5% to 29.6% by EG@ATH, in comparison to 27.5% by the physical mixture of EG and ATH (EG + ATH). Besides, EG@ATH exhibited better performance than EG + ATH on reducing the total smoke release and CO production. It is worth noticing that ATH could react with isocyanate groups, which was confirmed through FTIR. As a result, the interaction between the core-shell particles and the polymer matrix was enhanced, which protected the cell structure of RPUF from destroying by EG particles. The improved flame-retardant performance of EG@ATH, together with their low-cost, easy fabrication and especially friendliness to the environment, make it prospective in applications for flame retardancy of RPUF. Graphical abstract: A kind of core-shell expandable graphite @ aluminum hydroxide (EG@ATH) as the halogen-free flame retardant for rigid polyurethane foams (RPUF) was designed. This is the first report to prepare encapsulation of expandable graphite with inorganic nanomaterials to increase the expandability. The as-prepared EG@ATH particles showed high efficiency of flame retardancy in RPUF, and improved interface adhesion between EG@ATH particles and RPUF, due to the pre-reaction of ATH layers with polyisocyanate.